Reconstitution of T cell‐mediated immunity by umbilical cord‐derived mesenchymal stem cells in ulcerative colitis - Xiaoying Luo; Jieping Deng; Xiaoke Jiang; Jun Mi; Yangqiu Bai; Huimin Zhang; Yalong Li; Min Liu; Conghui Cai; Pengju Li; Huanrong Huang; Yueping Xu; et al. (Clinical and Translational Medicine)
Abstract Background Ulcerative colitis (UC) is an agnogenic chronic intestinal inflammatory disease. Umbilical cord‐derived mesenchymal stem cell (UMSC) is a potential therapeutic approach against UC; however, the mechanisms underlying their efficacy for UC remain unclear. Methods We performed a single‐arm clinical trial with 6 months follow‐up to assess the efficacy of UMSC in patients with moderate to severe left‐sided UC. The 26 enrolled patients were administered two UMSC doses intravenously. Pre‐ and post‐therapy colon biopsy specimens were analysed by single‐cell RNA sequencing (scRNA‐seq). Dextran sulphate sodium (DSS)‐induced colitis mouse models with or without UMSC injection were used to delineate colon inflammation and T cell function. Results In the clinical trial, the clinical response/remission rates were 80.8/46.2% and 75.0/37.5% after 2 and 6 months of therapy, respectively. Endoscopic and histological examinations showed improvement of colonic mucosa after UMSC therapy in responders. scRNA‐seq data showed that UMSC therapy may suppress pro‐inflammatory features of T lymphocytes and alleviate inflammatory responses by inhibiting the interaction of T cells with B and myeloid cells. In the murine experiment, UMSCs suppressed DUOX2‐mediated oxidative stress to attenuate DSS‐induced colitis by regulating T cell‐mediated immunity. Conclusion UMSC therapy primarily modulates T cell‐mediated immunity to achieve gut mucosal immune reconstitution and maintain mucosal barrier integrity, thereby achieving effective UC recovery. Highlights UMSCs effectively induce clinical remission in patients with active UC via T cell‐mediated immune reconstitution. scRNA‐seq analyses further revealed that UMSC therapy suppressed pro‐inflammatory features of T cells and alleviated inflammatory responses by inhibiting the interaction of T cells with B and myeloid cells UMSCs suppressed DUOX2‐mediated oxidative stress to attenuate DSS‐induced colitis by regulating T cell‐mediated immunity.